The Effect of Varying Water to Powder Ratios on the Microhardness and Microstructure of Mineral Trioxide Aggregate - Rethy Den; Rini Dharmastiti; Nuryono Nuryono; Leny Yuliatun; Widjijono Widjijono (Departmen Teknik Mesin dan Industri, Fakultas Teknik, Universitas Gadjah Mada, 2020)
The composition of water and powder in a mixture is one of the common problems in application as clinicians typically estimate the ratio chairside. The purpose of this study was to investigate the effect of varying water-to-powder ratios on the microhardness and microstructure of mineral trioxide aggregate (MTA). ROOTDENT MTA was investigated. One gram of cement was mixed with 0.28, 0.33, and 0.40 grams of distilled water and was stored for 1, 7, and 28 days in the water. Samples were subjected to x-ray diffraction (XRD), scanning electron microscopy (SEM), and microhardness tests. Tricalcium silicate, dicalcium silicate, zirconium dioxide, calcium carbonate, and calcium hydroxide were detected by XRD. SEM showed the presence of amorphous, porous capillary channel and capillary structure on the surface of the specimens. The SEM image for each water-to-powder ratio of the surface of the material was indistinguishable from the other. The highest microhardness was exhibited by the MTA specimen with the 0.33 water-to-powder ratio submerged in the water for 28 days.